Political Participation of the Communities of Blitar Regency in the 2020 Simultaneous Elections - Salahudin, Abdul Hakam; Widhiandono, Erwin; Kurniawan, Denny Arinanda (Politeknik Harapan Bangsa Surakarta, 2021)
The Covid-19 pandemic has changed patterns in all aspects of society, including its impact on political participation in society. Blitar Regency is a small example in several regions in Indonesia which carry out the 2020 simultaneous regional elections during the pandemic with a slightly different style from previous years. The purpose of the study was to determine the political participation of the Blitar district community in the 2020 simultaneous elections. The qualitative research method is a socio-political research with a normative-juridical approach with empirical data obtained from some information from informants who developed in the field. The results show that in a pandemic situation Covid-19 which has the potential to reduce public political participation in exercising their voting rights, it turns out that the Blitar Regency KPU is able to create a solution that is anticipatory, namely by implementing strict health protocols, and massive socialization either directly or digitally, so that it is able to approach the expected target, even higher from the previous two years. KPU, KPPS and the local community cooperate with each other to anticipate by trying to ensure health security during the simultaneous regional elections, also always trying to avoid possible frauds.